Calendar of Events. (Communications of the ACM, 2011)
A calendar of conferences and conventions connected to the Association for Computing Machinery (ACM) is presented, including the ACM SIGPLAN International Conference on Functional Programming, scheduled for September 18 through 24, 2011 in Tokyo, Japan; the ACM Symposium on Document Engineering, scheduled for September 19 through 22, 2011 in Mountain View, California; and the 30th International Conference on Computer Safety, Reliability, and Security, scheduled for September 19 through 21, 2011 in Naples, Italy.